Ultrafast decay dynamics of water molecules excited to electronic D̃′ and D̃′′ states: a time-resolved photoelectron spectroscopy study. Issue 27 (26th June 2019) - Min, Yanjun; Yang, Dongyuan; He, Zhigang; Chen, Zhichao; Yuan, Kaijun; Dai, Dongxu; Wu, Guorong; Yang, Xueming
Abstract : The ultrafast decay dynamics of water molecules excited to D̃′ and D̃′′ states is studied in detail. Abstract : The ultrafast decay dynamics of water molecules excited to D̃′ 1 B1 and D̃′′ 1 A2 states is studied by combining two-photon excitation and time-resolved photoelectron imaging methods. The lifetime of the D̃′ 1 B1 (000) state of H2 O (D2 O) is determined to be 1.54 ± 0.1 (22.6 ± 1.6) ps, consistent with a previous high-resolution spectroscopic study. The H2 O D̃′′ 1 A2 (000) state decays with a lifetime of 4.1 ± 0.2 ps, while in the D2 O D̃′′ 1 A2 (000) state, two independent decay pathways are observed, with time constants of 0.55 ± 0.1 and 13 ± 1 ps, respectively. The former is proposed to be associated with a hitherto undocumented D̃′′ → C̃ pathway, induced by Coriolis interaction.